2017
DOI: 10.1108/jpbm-07-2015-0939
|View full text |Cite
|
Sign up to set email alerts
|

Co-branding strategy in cause-related advertising: the fit between brand and cause

Abstract: Citation for published item:ruertsEqr¡ %D F nd venglerD tF nd gonsoli¡ onEegurD gF @PHIUA 9goErnding strtegy in useErelted dvertising X the (t etween rnd nd useF9D tournl of produt nd rnd mngementFD PT @PAF ppF IQSEISHF Further information on publisher's website: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 116 publications
(233 reference statements)
1
33
0
4
Order By: Relevance
“…Building on the theory of planned behaviour, both attitude and behavioural intentions are accepted as proxies for actual consumer behaviour (Ajzen & Fishbein, 1977). Attitude towards the co-branding entails the judgment and evaluation of the consumers' general feelings about the co-branded product (Garcia et al, 2017;James, 2006;Roswinanto, 2015;Senechal et al, 2014;Simonin & Ruth, 1998) whereas behavioural intention refers to the consumers' intention to purchase the co-branded product (e.g. Helmig et al, 2007;Mazodier & Merunka, 2014;Moon & Sprott, 2016;Rodrigue & Biswas, 2004); intention to recommend it to others (Ho et al, 2017) and willingness to pay (e.g.…”
Section: Liter Ature Re Vie Wmentioning
confidence: 99%
See 3 more Smart Citations
“…Building on the theory of planned behaviour, both attitude and behavioural intentions are accepted as proxies for actual consumer behaviour (Ajzen & Fishbein, 1977). Attitude towards the co-branding entails the judgment and evaluation of the consumers' general feelings about the co-branded product (Garcia et al, 2017;James, 2006;Roswinanto, 2015;Senechal et al, 2014;Simonin & Ruth, 1998) whereas behavioural intention refers to the consumers' intention to purchase the co-branded product (e.g. Helmig et al, 2007;Mazodier & Merunka, 2014;Moon & Sprott, 2016;Rodrigue & Biswas, 2004); intention to recommend it to others (Ho et al, 2017) and willingness to pay (e.g.…”
Section: Liter Ature Re Vie Wmentioning
confidence: 99%
“…Since marketing literature investigates brand attitude and behavioural intention as the success parameters for co-branding practice (e.g. Garcia et al, 2017;Helmig et al, 2008;Simonin & Ruth, 1998), this meta-analysis studies both of these variables as the dependent variables.…”
Section: Liter Ature Re Vie Wmentioning
confidence: 99%
See 2 more Smart Citations
“…An increasing number of companies are developing corporate social responsibility initiatives, in particular, CR-M practices (Huertas-García et al, 2017) because they have positive effects on consumers' behaviors (Sen and Bhattacharya, 2001;van den Brink et al, 2006) and attitudes (Barnes, 1992). In fact, in experimental studies (Koschate-Fischer et al, 2012;van den Brink et al, 2006), researchers found that compared to a control condition without CR-M, CR-M practices are more effective and have positive effects on brand-related outcomes.…”
Section: Consumers' Responses To Cause-related Marketingmentioning
confidence: 99%